2015
DOI: 10.32894/kujss.2015.102011
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in relation to some intestinal parasitic infection in children of Kirkuk city-Iraq

Abstract: Malnutrition and infection with intestinal parasites are widespread in almost all developing countries, high rate of people in the world are infected with protozoal and helminthes parasites. Most of cases are asymptomatic but some intestinal parasites can cause severe diarrhea and malnutrition problems. Four hundred and thirty children (257 male and 173 female) whom attended the parasitology section of Kirkuk General Pediatric and Azady Teaching Hospitals, were chosen for this study. Their ages were < 1-12 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
0
1
Order By: Relevance
“…The study considered children from different living areas, that relatively vary in the social environmental and economic conditions, to make it possible to relate the prevalence of the disease to the living conditions of those areas.Current study disclosed that the total incidence of the intestinal parasite infection was 19.778%. This is lower than what was reported by 15 and 3 who have reported infection incidences ratio of 24% and 22.27% respectively. However, the result presented here is higher than that of 16 and 17 who reported occurrence ratio of 14% and 17.4%, respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…The study considered children from different living areas, that relatively vary in the social environmental and economic conditions, to make it possible to relate the prevalence of the disease to the living conditions of those areas.Current study disclosed that the total incidence of the intestinal parasite infection was 19.778%. This is lower than what was reported by 15 and 3 who have reported infection incidences ratio of 24% and 22.27% respectively. However, the result presented here is higher than that of 16 and 17 who reported occurrence ratio of 14% and 17.4%, respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…The assessment of almost all academic research articles revealed during 2015 and confirmed a variation in the recording of E. histolytica infection among different provinces, high prevalence of infection (50.16%) was recorded in Sulaymaniyah (Ali, 2015), while the low prevalence of infection (5.52%) was recorded in Salahaddin (Tikrit) as mentioned by (Al-Ammash, 2015). Nearly similar results were recorded in Bbil, Al-Nasiria, Erbil, AL-Karbala and Kirkuk (23.37%, 23.78%, 24.4%, 26%, 26.32%, respectively) according to (Ali, 2015), (Khwam, 2015), (Faraj, 2015) (Fatima, 2018 and (Obaid, 2015). During 2016, a variation in the recording E. histolytica infection among different provinces had been demonstrated, similarly high prevalence of infection (79.49% and 70.1%), was recorded in Kirkuk and Diwania respectively (Ahmad, 2016) and (Al-Damerchi, 2016), while the low prevalence of infection (5.58%) was recorded in AL-Karbala (Muhsin, 2016).…”
Section: E Histolytica Schaudinn (1903)supporting
confidence: 76%